On globalization and business competitiveness: A panel data country classification - Hameed, Kamran; Arshed, Noman; Yazdani, Naveed; Munir, Mubbasher (Ascociacion Internacional de Economia Aplicada, 2021)
Industrial competitiveness could be achieved through policies reforms favoring globalization process. The reality, however, is two-folded. Initially, government policies restrict globalization and impose barriers to trade, restrict social and political activities. Structural reforms become inevitable to remain in the competition. Local resources, human capital, infrastructure, education and health facilities should be transformed. It is done through deploying a flexible structure that is adapting social, political and economic changes coming from the globalization process in order to make the local industry competitive. This paper argues that beneficiaries of globalization earn this status through strategizing and processing their resources into a competitive position. This gap is covered by empirically investigating the U-shaped relationship between globalization and competitiveness. Furthermore, categorizing the selected countries into under or over globalized nations.
Keywords: Anti-Globalization; Machine Learning (ML); Panel FGLS Algorithm